PEMANFAATAN KULIT KOPI MENJADI TEH CASCARA BAGI PENGUSAHA KOPI ROBUSTA GUNUNG MURIA - Yasin, Rozaq Muhammad; Fahira, Keke Tamara; Alpandari, Heny (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract The concept of sustainable agriculture is an important issue in the processing of agricultural products. One of the main ideas is the effort to utilize every agricultural product to become economically valuable. Coffee entrepreneurs are proficient in coffee sorting, roasting, grinding, packaging, and even marketing techniques that dare to use the marketplace. The purpose of this community service is to introduce innovation opportunities using coffee husks which were previously only thrown away to become processed cascara tea which has economic value. Through this activity, coffee entrepreneurs can utilize every part of the coffee harvest to be useful and of economic value. The targets of this activity are Muria Zayna coffee SMEs and Recolta SMEs in the Dawe sub-district, Kudus Regency. The activity method is carried out by providing training related to halal certification, market orientation, HR development and training of product innovation. The output of this activity is increasing market orientation through branding halal products and product innovation from coffee skins. In addition, through this activity it is able to support the concept of sustainable agriculture for coffee entrepreneurs. Abstrak Konsep suistanable agriculture menjadi isu penting dalam pengolahan hasil pertanian. Salah satu gagasan utamanya adalah upaya memanfaatkan setiap hasil pertanian menjadi bernilai ekonomis. Para pelaku usaha kopi sudah mahir dalam hal penyortiran kopi, roasting, grinding, packaging bahkan teknik pemasaran daring menggunakan marketplace. Tujuan pengabdian ini adalah memperkenalkan peluang inovasi menggunakan kulit kopi yang sebelumnya hanya dibuang menjadi sajian olahan teh cascara yang bernilai ekonomis. Melalui kegiatan ini, para pengusaha bisa memanfaatkan setiap bagian dari hasil panen kopi menjadi bermanfaat dan bernilai ekonomis. Sasaran kegiatan ini adalah pelaku UMKM kopi Muria Zayna dan UMKM Recolta yang berada di kecamatan Dawe Kabupaten Kudus. Metode kegiatan dilakukan dengan cara memberikan pelatihan terkait sertifikasi halal, orientasi pasar, pengembangan SDM dan kebutuhan inovasi produk. Luaran dari kegiatan ini adalah peningkatan orientasi pasar melalui branding produk halal dan inovasi produk dari kulit kopi. Selain itu, melalui kegiatan ini mampu mendukung konsep suistanable agriculture bagi pengusaha kopi.